Aspects of Studying Self-Adjustment of Mental States of the Employees of Internal Affairs Agencies of Ukraine within Professional Activity - T. L. Bilous (Law and Safety)
The article is focused on the research of self-regulation of mental states that arise in the employees of law enforcement agencies of Ukraine during the performance of professional activity in the conditions of extreme situations. The relevance of the research is currently increasing due to the need to increase resilience and overcome difficult life situations that often occur in the modern world.